OMahony, John (London, 2013)
2013 "OMahony, John", 2013, HistoryTalk John OMahony grew up on the White City estate in Shepherds Bush in the 60s and went to Christopher Wren School. His west London work career in the 70s and early 80s encompassed a paper round, a summer job at the Walls factory in Willesden, collecting glasses in the White City stadium Olympic bar at greyhound races, speedway meetings and pop concerts (including the Kinks and David Cassidy), a clerical job at the Post Office on Shaftesbury Avenue, a stint in the QPR shop at Loftus Road (in the Stan Bowles era), then Fidelity Radio and Brown Brothers car parts in Acton, the CBS record company warehouse in North Kensington, Whiteleys department store in Queensway, and Makro on Atlas Road.